Peningkatan Hasil Belajar Matematika Menggunakan Strategi Teka Teki Silang di SMP - Sinaryati Sinaryati (Lembaga Anotero Scientific Pekanbaru, 2022)
Background of The research by learning outcomes student which still many below Complete Criterion Minimize (CCM). Other than that study process only predominated by group owning high ability. Purpose of this research are to know do there are influence active learning strategy of crossword puzzle type to learning outcomes student of VIII.2 class SMP Negeri Bernas. Design of this research is classroom action research with research design repeated actions/cycles, each cycle consists of four steps (planning, implementation, observation and evaluation, reflection). The population in research was all student of VIII.2 class SMP Negeri Bernas. The data analysis technique used in this study is mastery learning after obtaining learning outcomes data through academic tests, then the data is data that describes student learning mastery. Result of this result was learning outcomes student after using active learning strategy of crossword puzzle type better of mean learning outcomes of student before using active learning strategy of crossword puzzle type.